Penerapan Sistem Antrian Multi Channel -Single Phase Menggunakan Model Simulasi Untuk Optimalisasi Pelayanan Pada UMKM El Laundry - Siska, Siska Pasaribu; Zaharuddin; Utama, Denny Walady (Jurnal Rekavasi, 2023)
ABSTRACT The queue process at UMKM El Laundry is a process related to the arrival of consumers who bring dirty clothes and then wait in line, then the dirty clothes are finished processing and the consumers leave the laundry. The current conditions at UMKM El Laundry are with an average number of arrivals of 20 people/day with the number of dirty clothes 20 kg/person. This has resulted in a buildup in serving consumers, where currently the service time limit applied by UMKM themselves is 8 hours/day for regular services. Data was obtained through observation for 1 month, namely in December 2022. The queuing method used is Multi-channel - single phase using Anylogic simulation. The results of calculations using the Multi-channel - single phase method show that queues occur due to lack of facilities in the process. After being analyzed using Anylogic simulation, it was proven that the queue could be minimized by adding washing machines, which were originally 3 units, to 4 units, and dryer machines, which were originally 3 units, to 4 units. So that the Queue Length which was originally 0.04 minutes became 0.94 minutes, Queue Time per agent from previously 0.50 minutes to 6.14 minutes, and service utilization which was originally 0.18 minutes to 0.75 minutes or 75% more fast in the service process, so that queues can be minimized. Keywords: MSME, Single Phase Multi Channel, Aylogic Simulation